(3GdQhV GdCfas - (3GdSgjdj , YHO GdQMef Hf YHO Gddg Hf CMeO Hf GUHZ GdNKYej CHh GdbGSe, CHh GdbGSe,J (B581 (3g` s
(3ChdgG (B:s
(3MeO Gddg ebOe Ydi cd CeQ Pi HGd hHYO aEfi GfJNHJ ai gPG GdEedGA HYO GSJNGQI eG hbY ai SjQI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hdf jHdZ HGdEWfGH ai eOM hdG QKGA cfg eMGSfg Udi Gddg Ydjg Ydi Bdg hSde Je GdcJGH s
(3Hg CKGQ JbWjYs
(3Hg fXGe GdJYbjHI HChdg ELGRGJs
(3cJH HNW ajg HYV GdVHW s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs